Elaboración de guion para spot publicitario para la carrera de Comunicación Social de la UTB - Rodriguez Muñoz, Prisila Jazmin (2019)
The literary script is one that contains a narration to be signed, in which dialogues of characters, time, stage, sound, plans, etc. are specified. The story that is told in it is so that the reader of the script is visible and understandable for both a producer and a director to bring it to reality through the screen. It is important to emphasize that to write a script you have to have clear ideas about what is going to be treated, bring the information in order and meet the objectives set for the transmission of the message you want to give. That is why, through observation and interview, an advertising script for the social communication career of the Technical University of Babahoyo is made, where previous proposals are analyzed and a new proposal is prepared based on the current needs of the career to publicize the profile of a student's graduation from it and thus demonstrate the abilities of their students in the professional field